PERTUMBUHAN CHROOCOCCUS DISPERSUS DALAM MEDIA LIMBAH CAIR PABRIK MINYAK KELAPA SAWIT (Jurnal Pelangi : Research of Education and Development, 2015)
Research on the effect of palm oil mill effluent medium on Chroococcus dispersus growth had been done.  The research was an experimental study with complete random design with 8 treatment (sediment and anaerob wastewater with concentration 25%, 50%, 75% and 100%). The growth curve was made based on the value of optical density (OD) measured at a wavelength of 680 nm. Chroococcus dispersus best growth seen at sediment wastewater medium with concentration of 100% and at anaerob wastewater medium with concentration of 75%.